The Threat of Carbapenem-Resistant Non-Fermenting Gram Negative Bacteria (NFGNB) - Saima Inam, Sadia Ikram, Syed Zeeshan Haider, Saba Shamim, Iram Yousaf Malik, Saleha Maqsood, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To Isolate Non fermenting Gram negative bacteria (NFGNB) from clinical specimens of infected patients in a tertiary care hospital and then determine the antimicrobial susceptibility of these isolates to Carbapenems Methodology: It was a Retrospective Cross-Sectional study conducted in the department of Pathology, of a tertiary care hospital, Lahore from December 2020-November 2021. The study included 4320 specimens received in Microbiology lab, for culture and sensitivity and consisted of urine, sputum, bronchial washings, pus, wound swabs, ETT, Folly’s catheter tip, HVS, body fluids, blood etc. All other specimens were inoculated on Blood agar (Oxoid UK), Mac Conkey agar (Oxoid UK), and urine was inoculated on CLED (Oxoid UK). The culture plates were incubated overnight at 37°C. Bacterial identification was achieved by gram staining, and biochemical profile. Analytical profile index API-20NE (Biomerieux, France) was used for non fermenting gram negative bacteria (NFGNB). Results: Four thousand three hundred and twenty specimens were processed and Gram negative bacteria were isolated in 651 cases constituting 15.1%. Out of these GNR, 130(19.97%) NFGNB were isolated. Maximum number of NFGNB were obtained from patients admitted in Surgery ward constituting 46 cases followed by Medical ward consisting of 38 cases, 15 cases each from ICU and OPD. Pus/wound swabs yielded majority of NFGNB 58(44.6%), followed by urine 33(25.3%), sputum 15(11.5%), and HVS 14(10.7%). Pseudomonas aeruginosa exhibited 35.29% and 32.35% resistance to meropenem (MEM) and imepenem (IPM) respectively. Conclusion: NFGNB are emerging pathogens responsible for variety of infections. These resilient pathogens have developed alarming resistance against the previously considered last therapeutic resort, carbapenems. Keywords: NFGNB, Carbapenems, Kirby Bauer disc diffusion method, CLSI, meropenem, imepenem,